2012
DOI: 10.1038/modpathol.2012.112
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial carcinoma with prominent squamous differentiation in the setting of neurogenic bladder: role of human papillomavirus infection

Abstract: Squamous cell carcinomas of the urinary bladder are rare in the Western world; the majority of cases are reported in countries endemic to Schistosoma parasitic infections. Unlike squamous tumors of the uterine cervix or oropharynx, the human papillomavirus (HPV) is not commonly associated with bladder squamous cell carcinomas. We report on two cases of HPV-positive urothelial carcinomas of the urinary bladder with extensive squamous differentiation showing the typical basaloid, poorly differentiated morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 71 publications
(99 reference statements)
0
28
0
6
Order By: Relevance
“…21 The presence of HPV infection in 2 cases of urothelial carcinoma with prominent squamous differentiation has recently been reported in the particular setting of neurogenic bladder. 25 HPV has also been associated with urothelial carcinoma in renal transplant recipients. 26 Considering these findings, it appears that any link between HPV and bladder neoplasia is more directly associated with particular clinical circumstances than as a general etiologic agent in the majority of bladder cancers.…”
Section: Discussionmentioning
confidence: 97%
“…21 The presence of HPV infection in 2 cases of urothelial carcinoma with prominent squamous differentiation has recently been reported in the particular setting of neurogenic bladder. 25 HPV has also been associated with urothelial carcinoma in renal transplant recipients. 26 Considering these findings, it appears that any link between HPV and bladder neoplasia is more directly associated with particular clinical circumstances than as a general etiologic agent in the majority of bladder cancers.…”
Section: Discussionmentioning
confidence: 97%
“…Squamous cell carcinoma is defined by the presence of intercellular bridges or keratinization and may be present in up to 40% of invasive urothelial carcinomas [63][64][65][66]. It is almost never associated with human papillomavirus infection, with the rare exception of some cases with a basaloid morphology [67,68]. Interestingly, recent genomic data have described a basal/squamous-like molecular subtype that has squamoid morphology and immunophenotype and is associated with poor survival and poor response to systemic therapy [69,70].…”
Section: Invasive Urothelial Carcinoma With Divergent Differentiationmentioning
confidence: 99%
“…Finally, a recent study identified a subset of urothelial carcinomas with coinfection of high-risk human papillomavirus (HPV) strains. 63 These tumors had a unique histomorphology, with prominent basaloid squamous-type differentiation, and commonly occurred in patients with neurogenic bladder. In situ hybridization for highrisk HPV strains can confirm coinfection in suspected cases (Fig.…”
Section: Molecular Oncogenesis Of Bladder Cancermentioning
confidence: 99%